Amber Brown wants extra credit - Danziger, Paula, 1944-2004 (Danziger, Paula, 1944-2004. A is for Amber., 1996)
Unhappy over her parents' divorce and her mother's boyfriend Max, nine-year-old Amber finds her schoolwork suffering.